Testing for majorana zero modes in a p(x) + ip(y) superconductor at high temperature by tunneling spectroscopy. - Kraus, Y; Auerbach, A; Fertig, H; Simon, S (2008)
Directly observing a zero energy Majorana state in the vortex core of a chiral superconductor by tunneling spectroscopy requires energy resolution better than the spacing between core states delta0(2)/epsilon F. We show that, nevertheless, its existence can be decisively tested by comparing the temperature-broadened tunneling conductance of a vortex with that of an antivortex even at temperatures T >> delta0(2)/epsilon F.